Paper making potential of Acacia dealbata and Acacia melanoxylon - Santos, António J. (2006)
The pulping and papermaking potential of Acacia dealbata and Acacia melanoxylon were studied using Eucalyptus globulus as a reference. Pulp yield, alkali consumption and delignification in the kraft process, of both species, compare very well with the reference. Pulp yield can be higher than that of E. globulus and the residual lignin content lower after cooking, which is in good agreement with the lower lignin and extractives content of the wood samples used. Pulps produced from Acacia have slightly lower fibre length and coarseness and higher fibre width and wet fibre flexibility than E. globulus pulps. As a consequence of fibre characteristics, the paper produced from Acacia is denser and exhibits higher tensile and burst strength, and lower tear resistance than that from E. globulus, at a given PFI revolution.